A multivariate analysis of SIEFORE daily returns - Roberto Calderón-Colín; Juan F. Carmona Sánchez (Banco de México, 2021)
This document presents a multivariate analysis of the relations among daily returns of pension funds in Mexico from 1997 to 2019. Evidence of a positive relation among daily returns through five statistical methods is provided. We find Granger causality of the returns of some funds to others, showing that some managers' decisions have influence on the investment decisions of others. We introduce financial connectedness indicators for daily returns, finding a high degree of linkage and spillovers. The high levels of financial connectedness observed suggests that shocks on the economy affect the SIEFORE returns in the same direction and broadly similar magnitude.
Keywords: G23; J32; 330; pension funds; private pension; financial stability